Pendidikan Kristen dalam Gereja Sebagai Dasar dan Sarana Aktualisasi Misi Kristen - Paulus Purwoto (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2021)
The role of believers and the church in actualizing the mission has a wrong mindset towards the basic concepts of missiology which results in not maximizing the preaching of the good news to others. Some people claim to be Christian but are reluctant to carry out the Great Commission and Paradigm that wrongly denounces the role of believers in evangelizing. For this reason, the church in Christian education is expected to be able to provide understanding to church members to be able to make Christian education the basis and means of evangelism. Using a qualitative descriptive approach, this research can be started by describing the mission and nature of the mission that Christian education must begin with an understanding related to the nature of missiology as the basis and driving force for the mission. Furthermore, the mission in Christian Education must also be a curriculum that is continuously taught to regenerate the Lord's congregation to continue to actualize the mandate of the Great Commission. so that the Church and Mission as a source of actualization can be realized and become the lifestyle of believers as part of the church.AbstrakPeran orang percaya dan gereja dalam mengaktualisasi misi memiliki mindset yang salah terhadap konsep dasar misiologi yang mengakibatkan tidak maksimalnya pemberitaan kabar baik bagi orang lain. Adanya orang yang mengaku Kristen, tetapi enggan untuk melakukan Amanat Agung dan Paradigma yang salah mengakibatkan tidak maksimalnya peran orang percaya dalam menginjil. Untuk itu gereja dalam pendidikan Kristen diharapkan mampu memberikan pemahaman kepada anggota gereja untuk dapat menjadikan pendidikan Kristen sebagai dasar dan sarana penginjilan. Menggunakan pendekatan kualitatif deskriptif penelitian ini dimulai dengan mendeskripsikan misi dan hakikat misi, selanjutnya pendidikan Kristen yang dimulai dengan pengertian yang berkaitan terhadap konsep dasar Misiologi sebagai motivasi atau penggerak dalam melakukan misi. Dan misi dalam Pendidikan Kristen juga harus menggunakan kurikulum misi yang terus diajarkan untuk meregenerasi jemaat Tuhan untuk terus mengaktualisasi mandat Amanat Agung. sehingga gereja dan misi sebagai sumber Aktualisasi dapat terwujud dan menjadi gaya hidup orang percaya sebagai bagian dari gereja.